2007
DOI: 10.1080/00268970701261431
|View full text |Cite
|
Sign up to set email alerts
|

Solvation by benzene: molecular dynamics simulation of orientational motion, translational diffusion, and site–site radial distributions of the solutes di- and trichloromethane (chloroform)

Abstract: By a standard, proven molecular dynamics procedure we generated individual equilibrium systems of dichloromethane and trichloromethane (chloroform) in benzene, each at equimolar concentration, as well as those of the neat components. We analysed the orientational dynamics of the C-H bond direction of chloroform in benzene-solvated and neat chloroform by the tumbling motion of its l ¼ 1 and l ¼ 2 Legendre polynomial auto-correlations between 250 and 438 K at iso-density conditions specific to the solution and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In this context, molecular dynamics (MD) simulations can complement experimental measurements to provide detailed, structural insights into the microscopic mechanism of solvation. 14,[37][38][39][40][41][42][43][44][45][46] In this work, we report a combined experimental and computational investigation of vibrational solvatochromism and spectral diffusion in small silane molecules in various solvents using Fourier transform infrared (FTIR) and 2D-IR spectroscopies. To elucidate substituent effects on solvation dynamics, trimethoxysilane (TriMOS) and triphenylsilane (TriPS) were chosen in our study since the same vibrational mode can be monitored in the presence of different electron withdrawing ligands, giving rise to different solvatochromic responses.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, molecular dynamics (MD) simulations can complement experimental measurements to provide detailed, structural insights into the microscopic mechanism of solvation. 14,[37][38][39][40][41][42][43][44][45][46] In this work, we report a combined experimental and computational investigation of vibrational solvatochromism and spectral diffusion in small silane molecules in various solvents using Fourier transform infrared (FTIR) and 2D-IR spectroscopies. To elucidate substituent effects on solvation dynamics, trimethoxysilane (TriMOS) and triphenylsilane (TriPS) were chosen in our study since the same vibrational mode can be monitored in the presence of different electron withdrawing ligands, giving rise to different solvatochromic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their relevance to reaction dynamics, the fast restructuring events that occur in the solvent are often poorly characterized due, in large part, to the challenges associated with the measurements and the interpretation of the resulting data. Important insight into the microscopic processes in neat solvents has been gleaned from molecular dynamics (MD) simulations. In turn, these simulations have been validated and refined by experimental observables from higher-order spectroscopies such as optical Kerr effect, fluorescence Stokes shift, , RaPTORS, and photon echo spectroscopies. , Two-dimensional IR (2D-IR) spectroscopy has emerged as a powerful experimental approach to characterizing the dynamics in the vicinity of a solute molecule. In a 2D-IR experiment, an IR-active chromophore or functional group is viewed as a reporter of the local solvation environment. This is often modeled by the vibrational Stark effect, whereby the time-dependent electrostatics of the surrounding molecules induce frequency shifts with the characteristic time scales of the solvation dynamics. By preparing a coherent collection of vibrations in the sample and allowing those ensembles to experience their surrounding environments for varying lengths of time before recovering the surviving oscillators in the form of a rephased vibrational echo signal, the associated molecular dynamics are obtained as vibrational dephasing and spectral diffusion from amidst the heavily inhomogeneously broadened environments that are common in the condensed phase.…”
Section: Introductionmentioning
confidence: 99%
“…31 In the 2000s, interest in this complex resurfaced and efforts to prove or disprove the presence of this complex in the liquid state using MD simulations began. Rothschild 32,33 concluded that the structure proposed by earlier researchers like Reeves and Schneider (with the c axis of chloroform pointing toward the center of the ring plane of benzene) has a "near-vanishing" probability to exist in solution.…”
Section: Calculated Correlation Factors Frommentioning
confidence: 98%